Fast and precise targeting of single tumor cells in vivo by multimodal correlative microscopy - Karreman, Matthia A.; Mercier, Luc; Schieber, Nicole L.; Solecki, Gergely; Allio, Guillaume; Winkler, Frank; Ruthensteiner, Bernhard; Goetz, Jacky G.; Schwab, Yannick (Journal of cell science, 2016)
Skip to Next Section - Intravital microscopy provides dynamic understanding of multiple cell biological processes, but its limited resolution has so far precluded structural analysis. Because it is difficult to capture rare and transient events, only a few attempts have been made to observe specific developmental and pathological processes in animal models using electron microscopy. The multimodal correlative approach that we propose here combines intravital microscopy, microscopic X-ray computed tomography and three-dimensional electron microscopy. It enables a rapid (c.a. 2 weeks) and accurate (<5 µm) correlation of functional imaging to ultrastructural analysis of single cells in a relevant context. We demonstrate the power of our approach by capturing single tumor cells in the vasculature of the cerebral cortex and in subcutaneous tumors, providing unique insights into metastatic events. Providing a significantly improved throughput, our workflow enables multiple sampling, a prerequisite for making correlative imaging a relevant tool to study cell biology in vivo. Owing to the versatility of this workflow, we envision broad applications in various fields of biological research, such as cancer or developmental biology.
Gesehen am 07.05.2020